2019
DOI: 10.1136/sextrans-2019-054058
|View full text |Cite
|
Sign up to set email alerts
|

ExtragenitalMycoplasma genitaliuminfections among men who have sex with men

Abstract: ObjectivesThere are limited data on the prevalence of Mycoplasma genitalium (Mgen) coinfection with rectal chlamydia (Chlamydia trachomatis (CT)) and rectal gonorrhoea (Neisseria gonorrhoeae (NG)) infections and few studies examining the prevalence of pharyngeal Mgen in men who have sex with men (MSM). Using transcription-mediated amplification assay, this study aimed to determine the proportion of rectal CT and rectal NG infections in MSM who are coinfected with rectal Mgen, and the proportion of MSM with Mge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 25 publications
3
16
0
Order By: Relevance
“…trachomatis coinfections in this study (9.2%) was slightly lower than has been previously reported (13%). 1 However, a high prevalence of macrolide resistance was detected, comparable with that detected by the PHE reference service overall in 2018 (table 1). Further to this, evidence of resistance to fluoroquinolones was also found.…”
Section: Prevalence Of Chlamydia Trachomatis and Mycoplasma Genitaliusupporting
confidence: 62%
See 1 more Smart Citation
“…trachomatis coinfections in this study (9.2%) was slightly lower than has been previously reported (13%). 1 However, a high prevalence of macrolide resistance was detected, comparable with that detected by the PHE reference service overall in 2018 (table 1). Further to this, evidence of resistance to fluoroquinolones was also found.…”
Section: Prevalence Of Chlamydia Trachomatis and Mycoplasma Genitaliusupporting
confidence: 62%
“…To the Editor-in-Chief It has recently been reported that 13% of men who have sex with men (MSM) attending a sexual health clinic were coinfected with Chlamydia trachomatis and Mycoplasma genitalium in the rectum, 1 a site that has been described as a reservoir for asymptomatic M. genitalium infection. 2 Public (table 1).…”
Section: Prevalence Of Chlamydia Trachomatis and Mycoplasma Genitaliumentioning
confidence: 99%
“…Consequently, there is uncertainty around the need to treat asymptomatic MSM, particularly as extended-spectrum fluoroquinolones are costly, often hard to access in the community, and may cause severe side effects [7,28]. However, asymptomatic carriage of M. genitalium, particularly at the rectum, and exposure to antibiotics for treatment of other sexually transmitted infections can contribute to the development and spread of resistant M. genitalium [7,42]. The period of time for asymptomatic infections in men to resolve spontaneously is also unknown, but infections may persist for prolonged periods even after symptom resolution [2,43].…”
Section: Discussionmentioning
confidence: 99%
“…[19,20] Individuals with chlamydia or gonorrhoea are frequently co-infected with Mg (as was the case for 20% in our study), which increases the probability of bystander antimicrobial selection pressure and which, in part, may explain the high prevalence of macrolide RAMs found in MSM. [4,21,22]…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review and meta-analysis up to 2017 found the prevalence of Mg to be 0.9% in pregnant women, 3.2% in MSM and 15.9% in female sex workers. [2] The prevalence of Mg in MSM, is, however, now reaching 10% according to the most recent publications. [3][4][5][6] Mg is a cause of non-gonococcal urethritis in men and cervicitis in women, but Mg is also frequently found in asymptomatic individuals.…”
Section: Introductionmentioning
confidence: 99%